Síntese e caracterização de novos polímeros baseados em poli(arileno éter sulfona) sulfonados reticulados e produção de membrana para aplicação em células a combustível do tipo PEMFC - Júlio Cesar de Souza (2016)
In the present work a comprehensive literature review on fuel cells and, in particular, of the fuel cell with polymer electrolyte (PEMFC) was carried out. They addressed issues related to its operating principle, its constituents, mode of operation, advantages and limitations. Then,the review was focused on polymeric proton exchange membranes (PEM). Aspects such as the development history of polymer types and results were addressed. From this review, it was found that the crosslinked polymeric membranes have great potential for application inPEMFC. These membranes have key features to meet industry needs, like high proton conductivity with low humidification, allowing its operation in high-temperature fuel cells. The polymers based on poly(arylene ether sulfone)s sulfonated (SPAES) have shown promising results and such systems were chosen to be studied. We opted for the synthesis of acrosslinkable SPAES synthesized by polycondensation of the monomers bisphenol A (BFA), 2,2'-diallylbisphenol A (ABFA), bis(4-chlorophenyl) sulfone (CFS) and bis(6-sulfonate,4 chlorophenyl)sulfone sodium salt (SCFS). The monomers BFA and CFS were purchased in the market and analyzed by FTIR and TG techniques, which showed its direct applicability in the synthesis. The monomer ABFA also purchased in the market was analyzed by FTIR, TG and HPLC techniques, whereby it was found that the presence of contaminants with only one reaction point could be limiting for the polymerization. This effect was, however, droppedlater in the light of further evidence. The monomer SCFS was synthesized from CFS and analyzed by FTIR, TG and DSC techniques, whose results showed its high hygroscopicity. From the four monomers it was carried out the synthesis of polymers with different degrees of sulfonation and crosslinking provided by the different combination of the proportions ofmonomers. The route of synthesis of the polymers was studied and optimized, since the ordinary route proposed in the literature, did not prove effective. During this step it was found that the polymerization reaction occurred effectively, however, that obtained polymers had become soluble in water, contrary to expectation based on the literature. The polymers recovery process has been studied and a new process based on the destabilization of the solution in an acid medium has been proposed. Nine polymers were finally synthesized with good mass yields, based on a Design of Experiments model with two factors (ABFA andSCFS monomer content) and three levels (25%, 50% and 75%). These polymers were crosslinked by thermally initiated crosslinking with benzoyl peroxide. From these polymers, It has been found that four showed negative crosslinking results, which was associated with the quality of the SCFS monomer. The five other crosslinked polymers showed dry appearance, brittle and crumbly. In characterization tests by FTIR were observed the characteristic bands of monomers ABFA and SCFS, indicative of its incorporation into the polymer. The proportion of monomers ABFA in the polymers suggested the possibility of different incorporation of monomers into the polymers which may have effects oncrosslinking efficiency of the polymer. Gel fraction tests showed satisfactory crosslinking results, higher than 70% w / w. The thermogravimetric analysis (TG) showed the presence of contamination with synthesis solvents in addition to moisture, especially of those polymers not addressed to its acid form. Furthermore, the TG showed that all polymers are stable at temperatures above 300 °C. The tests by differential scanning calorimetry (DSC) corroborated the observations obtained by means of TG. The assays for the determination of ion exchange capacity (IEC) of the crosslinked polymers exhibit low incorporation of monomers SCFS, which was attributed to the selective incorporation of the monomers during polymerization. Moisture absorption and swelling tests showed promising results for polymers with lower SCFS content, direct and undeniable reflection of low incorporation of monomers SCFS, however. On the other hand, polymers with higher levels SCFS showed high rates of water absorption and swelling, particularly at elevated temperatures, even resulting in fragmentation and loss of mechanical properties. The results suggested a fall in polymer crosslinking density, despite the good gel fraction results obtained. Thus, the polymers obtained and studied were weak and brittle, with low potential for proton conductivity and high tendency to moisture absorption and swelling, proving to be inadequate for the intended application. The results showed that the studied systems need to be more fully understood, particularly with regard to the degree of polymerization and the structural regularity (block copolymers or random). These features are essential for a better understanding of the polymers and their behavior aimed at adjusting the polymerization synthesis route and crosslinking, in order to obtain suitable materials for PEMFCs.